Pemanfaatan Serbuk Kaca Sebagai Peningkatan Waterproofing pada Bahan Tambah Cat - Fikri Haekal; Ismail Aqil M.S.; Riza Susanti; Hartono Hartono (Universitas Diponegoro, 2024)
In the construction of a project, walls account for approximately 20% - 40% of the total budget. Wall works are considered costly as they involve various tasks such as brick installation, plastering, rendering, and painting. Nowadays, the use of paint is widespread in line with the development of construction projects in Indonesia. Paint utilization has been extensively developed with various innovations, one of which is waterproofing paint that can protect surfaces from water or moisture. By adding a special ingredient to the paint to enhance its waterproofing properties, wall paint becomes more resistant to rain exposure over time. Therefore, the addition of glass powder to the paint mixture is needed to increase the waterproofing level because glass powder has nonporous characteristics, meaning it does not easily absorb or retain water. The objective of this research is to determine the water resistance of paint with the addition of glass powder at levels of 0%, 2,5%, 5%, 7,5%, and 10% in each 1 kg paint sample. The most optimum paint formulation is achieved by adding a 10% glass powder content, resulting in water leakage test of 0 mL, adhesion test of 5A, water absorption of 6.587%, specific gravity of 2.092 g/mL, coverage of 5.553 m²/Kg, and drying time of 4 minutes. This study aims to contribute to the development of high waterproofing wall paint that is also environmentally friendly.